Isolation and identification of pathogens of wild garlic (Allium sativum L.) - Astorga-Quirós, Karina (2014)
The garlic field (Allium sativum L.) in Costa Rica could become a profitable alternative for the production and diversification of the vegetable farmers. However, the type of vegetative propagation that it presents facilitates the transmission and dissemination of diseases, which produces a progressive weakening of the bulbs. Currently, different options from chemical control are being searched, in order to reduce the ecological and environmental impact of the pathogens to it. Biologic control is one of them, but it presents difficulties in the isolation and accurate identification of pathogens associated to the decay that occurs in the soil. Therefore, the general objective of this research was to isolate and identify, at a species level, strains of Pseudomas marginalist, Peniciliium sp. and Sclerotium cepivorum, from vegetative material of garlic in field, for its utilization in future studies of biologic control of these diseases. The followed methodology allowed us to isolate and identify P. marginalis with a high accurate percentage. Also, it allowed us to obtained single-spore cultures of Penicillium sp. and pure cultures of S.cepivorum. The described techniques constituted the basis for future works related to the plant diseases in the garlic production.